2014
DOI: 10.1093/heapol/czu054
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stakeholder values and power relations on community-based health insurance coverage: qualitative evidence from three Senegalese case studies

Abstract: Continued low rates of enrolment in community-based health insurance (CBHI) suggest that strategies proposed for scaling up are unsuccessfully implemented or inadequately address underlying limitations of CBHI. One reason may be a lack of incorporation of social and political context into CBHI policy. In this study, the hypothesis is proposed that values and power relations inherent in social networks of CBHI stakeholders can explain levels of CBHI coverage. To test this, three case studies constituting Senega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…This largely left the VHTs dependent on the formal health care providers for executing the referrals. In Senegal, Mladovsky et al found that the dependency of community-based health insurance (CBHI) schemes on hospitals left the CBHI schemes with little negotiating power for their goals and interest [57]. In countries like Pakistan, the Lady Health Worker programme was hailed as effective partly because the programme invested in, among other things, maintaining strong ties with existing community resources such as traditional birth attendants [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This largely left the VHTs dependent on the formal health care providers for executing the referrals. In Senegal, Mladovsky et al found that the dependency of community-based health insurance (CBHI) schemes on hospitals left the CBHI schemes with little negotiating power for their goals and interest [57]. In countries like Pakistan, the Lady Health Worker programme was hailed as effective partly because the programme invested in, among other things, maintaining strong ties with existing community resources such as traditional birth attendants [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study also shows that attention needs to paid to how the incentives given to the CHWs can affect the trust of community members over time. Mladovsky et al, for example, show that ‘volunteering by CBHI staff built trust in CBHI among the target population.’ ([57] p. 776). While the VHTs were recruited as volunteers, some community members perceived them as drawing salaries from the government, and in practice, their work is facilitated leading to a perception that they occupy a privileged position.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous study results highlighting the weak bargaining power of MHOs in their relationship with providers. Reasons evoked in this earlier work are their relative insignificance for hospital finances [23], a position of monopoly of providers in rural areas [24], and power imbalances [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…By design, the voluntary aspect was very clear; but when it came to implementation, the responsibilities were left to local government leaders, who created a sense of compulsory enrolment in some areas. Although the involvement of community leaders may have had a positive impact on the uptake of CBHI schemes, sometimes, they exerted coercive mechanisms that may have contradicted the voluntary nature of CBHI schemes . In our case, we have seen imposed participation (both by design and by practice) that created a sense of obligation for some participants in both CHF cases.…”
Section: Discussionmentioning
confidence: 99%
“…The common demand side features that influence enrolment decisions include social‐economic and demographic factors, especially those related to access to and quality of healthcare; knowledge on health insurance; and willingness and ability to pay . On the supply side, attention has been paid to schemes' design and management issues, where premium prices, benefit packages, methods of premium collection, and administration capabilities have been reported to affect CBHI uptake . The voluntary nature of CBHI schemes has also been described as challenging their sustainability, since people who experience illness appear to be more interested, resulting in a low rate of participation of healthy population groups .…”
Section: Introductionmentioning
confidence: 99%